Integrating Artificial Intelligence and Nanotechnology for Precision Cancer Medicine. Issue 13 (9th July 2019) - Adir, Omer; Poley, Maria; Chen, Gal; Froim, Sahar; Krinsky, Nitzan; Shklover, Jeny; Shainsky‐Roitman, Janna; Lammers, Twan; Schroeder, Avi
Abstract: Artificial intelligence (AI) and nanotechnology are two fields that are instrumental in realizing the goal of precision medicine—tailoring the best treatment for each cancer patient. Recent conversion between these two fields is enabling better patient data acquisition and improved design of nanomaterials for precision cancer medicine. Diagnostic nanomaterials are used to assemble a patient‐specific disease profile, which is then leveraged, through a set of therapeutic nanotechnologies, to improve the treatment outcome. However, high intratumor and interpatient heterogeneities make the rational design of diagnostic and therapeutic platforms, and analysis of their output, extremely difficult. Integration of AI approaches can bridge this gap, using pattern analysis and classification algorithms for improved diagnostic and therapeutic accuracy. Nanomedicine design also benefits from the application of AI, by optimizing material properties according to predicted interactions with the target drug, biological fluids, immune system, vasculature, and cell membranes, all affecting therapeutic efficacy. Here, fundamental concepts in AI are described and the contributions and promise of nanotechnology coupled with AI to the future of precision cancer medicine are reviewed. Abstract : Artificial intelligence (AI) and nanotechnology are instrumental in realizing the goal of precision medicine—tailoring the best treatment for each cancer patient. Recent conversion between these fields is enabling better patient data acquisition and improved design of nanomaterials. Fundamental concepts in AI and the contributions of nanotechnology and AI to the future of precision cancer medicine are reviewed.